Silencing of microRNA-101 prevents IL-1β-induced extracellular matrix degradation in chondrocytes - Dai, Linghui (BioMed Central, 2012)
INTRODUCTION: Extracellular matrix (ECM) degradation leads to malfunction of the cartilage in osteoarthritis (OA). Inflammatory cytokine interleukin-1 beta (IL-1β) functions in ECM degradation and prevents ECM synthesis by down-regulating the key transcription factor, Sox9, and consequently inhibiting ECM gene expression. Evidence reveals that microRNAs (miRNA) have been associated with OA, but little is known of their function in chondrocyte ECM degradation. This study aimed to identify possible miRNAs that mediate IL-1β-induced down-regulation of Sox9 as well as its known down-stream genes, collagen type II and aggrecan. METHODS: The miRNAs were predicted based on three classical databases. The expression levels of the predicted miRNAs were assessed in IL-1β stimulated chondrocytes by real-time PCR. A luciferase reporter was used to test the binding of the miRNAs to the 3' untranslated regions (3'UTR) of Sox9. The predicted miRNAs were transfected into chondrocytes to validate their relationship with Sox9. Functional analysis of the miRNAs on chondrocytes ECM degradation was performed at both the mRNA and protein levels after miRNA transfection and IL-1β treatment. RESULTS: Six miRNAs were predicted to target Sox9, and their expression in IL-1β-stimulated chondrocytes was revealed by real-time PCR. The luciferase reporter assay indicated that only miR-101 could bind to the 3'UTR of Sox9. The expression of Sox9 was likewise negatively regulated by miR-101 in rat chondrocytes. Functional analysis showed that miR-101 could aggravate chondrocyte ECM degradation, whereas miR-101 inhibition could reverse IL-1β-induced ECM degradation. CONCLUSION: miR-101 participates in IL-1β-induced chondrocyte ECM degradation. Down-regulating miR-101 expression can prevent the IL-1β-induced ECM degradation in chondrocytes. miR-101 probably functions by directly targeting Sox9 mRNA.